3D modelling of electromagnetic fields: advantages and disadvantages of nodal or edge elements. (4th August 2014) - Bandelie, B.; Rioux–Damidau, F.
Starting from the magnetic field formulation of magnetodynamics, we consider the coupling of a finite element method in the conductors with a boundary integral method for the description of the exterior region. We examine three different discretizations: one variable per edge, two variables per edge and nodal variables. We determine the precision on the magnetic field h and the current j = curl h as a function of the dimension of the mesh and of the CPU time in each case. We deduce the best–suited variable to the computation of each physical quantity.